The beginnings of the collective identity of Slovaks in the Central European context - Káša, Peter (Slavica, 2024)
The study analyses the linguistic, literary and cultural contexts of the formation of Slovak national identity during the Enlightenment and the early national movement. The Slovak intellectual elite identified and defined Slovaks and the Slovak nation in terms of modern Austrian statehood, traditional Hungarian patriotism and cultural Slavism. The study shows that modern Slovak nationalism was already richly structured atits beginnings, adopting diverse ideological impulses and establishing relations with neighboring Slavic and non-Slavic cultures.